2024
DOI: 10.1002/aic.18431
|View full text |Cite
|
Sign up to set email alerts
|

Propane dehydrogenation on Ir single‐atom catalyst modified by atomically dispersed Sn promoters in silicalite‐1 zeolite

Ying Zhang,
Shaolin Shi,
Ziyue Wang
et al.

Abstract: Propylene serves as a crucial feedstock for a wide range of industries engaged in the production of diverse petrochemical products. Propane dehydrogenation, an appealing technology aimed at supplanting conventional methodologies, confronts significant hurdles attributable to coke deposition and sintering in Pt‐based catalysts. Here, we report an Ir single atom encapsulated in silicalite‐1 zeolite modified with Sn single atoms as electronic promoters, displaying remarkable activity and stability, which is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…Sommerville and Shapley [16] detected the formation of bimetallic Ir-Sn particles via the EDX analysis of IrSn/zeolite catalysts. Finally, Zhang et al [17] confirmed using XANES and EXAFS results that the introduction of Sn atoms promotes the transfer of electrons from Sn atoms to Ir atoms, forming electron-rich Ir δ+ species. Another factor to take into account is based on studies about the formation of bimetallic complexes containing Ir and Sn during the preparation of the catalysts.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sommerville and Shapley [16] detected the formation of bimetallic Ir-Sn particles via the EDX analysis of IrSn/zeolite catalysts. Finally, Zhang et al [17] confirmed using XANES and EXAFS results that the introduction of Sn atoms promotes the transfer of electrons from Sn atoms to Ir atoms, forming electron-rich Ir δ+ species. Another factor to take into account is based on studies about the formation of bimetallic complexes containing Ir and Sn during the preparation of the catalysts.…”
Section: Discussionmentioning
confidence: 92%
“…Considering the properties of high thermal stability, resistance to deactivation by coke and the possibility of inhibiting its hydrogenolytic properties with a promoter metal, Ir seems a good candidate to be studied for the direct dehydrogenation of light paraffins such as n-butane. Indeed, IrSn catalysts, supported on different materials like zeolite and silica, showed good behavior in propane dehydrogenation [12,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In the direct propane dehydrogenation reaction, the established catalysts mainly include Pt-, V-, Zn-, Mo-, Cr-, Ir-, Co-, and Ga-based catalysts, and they presented good to excellent performances in the reaction. For instance, a MgO-modified ZnO x /Silicalite-1 and a ZnFe 2 O x /Silicalite-1 could prevent the active site from leaching and coke formation by inhibiting the carbon deposit formation via strong interactions between active metal and supports. , Among them, Ga-based catalysts have been widely studied for ODHP.…”
Section: Introductionmentioning
confidence: 99%